Penerapan Prinsip Kepentingan Terbaik bagi Anak pada Hak Asuh Anak Pasca Perceraian (Studi Putusan Mahkamah Agung Nomor 395 K/AG/2020) - Sri Wahyuni (Jurnal Hukum Lex Generalis, 2025)
Divorce is the termination of a marriage by a court decision or at the request of one of the partners. One of the impacts of a failed marriage due to divorce is related to custody. Determination of the granting of child custody due to divorce should be carried out by applying the principle of the best interests of the child (Best Interest of Child) because basically the relationship between children and parents is not broken due to divorce. The consequence of the end of a marriage due to divorce is that both the mother and father are still obliged to care for and educate their children, solely based on the interests of the child if there is a dispute regarding the control of the children, the court makes a decision. The research method used in this study is the doctrinal method, using the type of normative juridical research. The results of the study indicate that the Supreme Court Decision Number 395 K/AG/2020 did not apply Article 105 of the Compilation of Islamic Law which states that children who are not yet 12 years old or not yet mummayiz are the rights of their mothers. However, the author believes that Article 105 letter a of the Compilation of Islamic Law can be applied to this case because in this decision, both in the considerations and evidence, there is nothing that can cause the mother to lose custody of the child. This is also reinforced by the fact that the divorce was filed on the husband's initiative and it was not proven that the wife was the cause of the rift in the household.